Teaching students of technical universities how to solve differential equations on matlab program: Teaching students of technical universities how to solve differential equations on matlab program - Sodikkhujaeva, Sh.Kh. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation. The main scientific idea of this work is taught students in technical higher education how to solve second order differential equation in program MATLAB.